Analysis of water polo injuries during 8904 player matches at FINA World Championships and Olympic games to make the sport safer. Issue 1 (10th January 2019) - Mountjoy, Margo; Miller, Jim; Junge, Astrid
Abstract : Objective: To analyse injuries of water polo players reported during four Summer Olympic Games (2004, 2008, 2012, 2016) and four Federation Internationale de Natation World Championships (2009, 2013, 2015, 2017). Methods: Injuries during training and matches were reported daily by the team physicians and the local medical staff at the sports venues using an established surveillance system. Results: A total of 381 injuries were reported, equivalent to 14.1 injuries per 100 players (95% CI ±1.42). The most frequent diagnoses were laceration (12.7%) and contusion (10.9%) of head, followed by (sub-)luxation/sprain of hand (9.5%) and contusion of trunk (6.5%) or hand (6.2%). More than half of the injuries (57.0%) occurred due to contact with another player. A quarter of the injuries (25.4%) were expected to result in absence from training or match; 10 (2.9%) resulted in an estimated time-loss of 3 or more weeks. About three-quarters of injuries (75.6%) occurred during matches, 86 during training. The incidence of match injuries was on average 56.2 injuries per 1000 match hours (95% CI ±6.74). The incidence of time-loss match injuries (14.7; 95% CI ±3.44) was significantly higher in men than in women. Conclusions: A critical review of water polo in-competition rules and the implementation of a Fair Play programme may help to mitigate the high incidence of contact injuries incurred during matches. A water polo-specific concussion education programme including recognition, treatment and return to play is recommended. Finally, a prospective injury surveillance programme would help to better define water polo injuries outside of the competition period.